Perancangan Media Pembelajaran Non Formal Desain Elementeer Berbasis Media Interaktif - EKA PUTRI YOLANDA, Dr. Syafwandi, M.Sn., Riri Trinanda, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
The purpose of this design is to design non-formal learning media for interactive media-based elementary design. This interactive media learning is designed as a design solution to help the development of creativity and help to increase the reading interest of the target audience, namely the millennial generation. The method of designing interactive learning media is carried out with an analysis of 5W + 1H whose data is obtained from field observations such as millennial generation activities and interactions when receiving the learning process. This presentation produces an informal media based on interactive media-based elementary design as the main media, and also supported by several other media, namely: X-banners, posters, stickers, pouches, T-shirts, notebooks as the main media support and promotional media.Keywords: Interactive media, non-formal learning, elementary design.